ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN KIMIA: Materi Reaksi Redoks dan Elektrokimia MENGGUNAKAN MODEL PROBLEM BASED LEARNING - Muhamad Rosid (FKIP Universitas Jember, 2019)
Abstract: This study aimed to analyze the learning activities of students inthe chemistry learning process by using the problem base learning (PBL)learning model. This research was an experimental study using ControlGroup Design on 12th grade science students at High School TegaldlimoBanyuwangi, East Java. As a control class was class 12 IPA-1 and as anexperimental class was class 12 IPA-2. Learning chemistry of redox andelectrochemical reaction materials in the experimental class used theproblem base learning model, while learning in the control class did not usethe problem base learning model. Aspects of critical thinking skills reviewedinclude 3 aspects: (1) Elementary clarification (giving basic explanations),which was about what known and what the core problem; (2) The basis forthe decision (determining the basis for decision making), namely the rightreasons as the basis before a step was taken; (3) Inference (drawingconclusions), namely drawing correct conclusions must be based on reasonsthat are reasonable or logical. Student learning activities during the studywere also observed to include: 1) involvement in discussion, 2) involvementin carrying out practicum, 3) discipline in learning, 4) responsibility. Theresults of the analysis using the t-Test statistical analysis with a 95%confidence level proved that the students' ability to provide explanations,decision making, and the ability to draw conclusions in the experimentalclass students were significantly higher than those in the control class.Keywords: Problem Based Learning Model, Critical Thinking Ability